Exploration of Handling English Learning Difficulties on SMP Students During the Covid-19 Pandemic - Tamar Pangarungan; Nurdin Arsyad; Priska Efriani Luansi Ero (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The COVID-19 pandemic has caused various learning difficulties for students, including English language learning. Therefore, proper handling is needed to resolve these difficulties. This study aims to describe the handling of school principals, teachers, and parents in addressing English language learning difficulties of junior high school students during the COVID-19 pandemic. Data was collected through structured interviews with informants who are school principals, teachers, and parents of students at SMP Negeri 1 Tikala and analyzed using the Miles and Huberman qualitative analysis scheme, with stages of data collection, data reduction, data exposure, and conclusion drawing. Based on the interview with the school principal, handling was done by providing data quota assistance for teachers and students, providing free Wi-Fi in the school area, issuing policies for learning that can be done both online and offline. Based on the interview with teachers, handling was done by providing motivation to students through ice breaking activities and rewards, personal communication with students who have problems, presenting lessons using fun methods. Based on the interview with parents, handling was done by providing supporting facilities for student learning such as communication tools or tools that support English language learning, providing guidance to students, communicating with teachers to understand the student's progress, and finding solutions to any difficulties experienced by the students.